Sleep-wake differences in scaling behavior of the human heartbeat: Analysis of terrestrial and long-term space flight data - Ivanov, P. Ch; Bunde, A; Amaral, L. A. N; Havlin, S; Fritsch-Yelle, J; Baevsky, R. M; Stanley, H. E; Goldberger, A. L (Europhysics letters, 1999)
We compare scaling properties of the cardiac dynamics during sleep and wake periods for healthy individuals, cosmonauts during orbital flight, and subjects with severe heart disease. For all three groups, we find a greater degree of anticorrelation in the heartbeat fluctuations during sleep compared to wake periods. The sleep-wake difference in the scaling exponents for the three groups is comparable to the difference between healthy and diseased individuals. The observed scaling differences are not accounted for simply by different levels of activity, but appear related to intrinsic changes in the neuroautonomic control of the heartbeat.